LAUT YANG MENYATUKAN: MENGUNGKAP RUANG-JEJARING LAUT MALUKU - Alex John Ulaen (Fakultas Ilmu Budaya universitas Hasanuddin, 2017)
Maritime transportation has the role of unifying one coast with another and allowing population mobility. The existence of various communities from Nusantara or overseas in coastal cities in Sulawesi and Maluku since five centuries ago confirms what Lombard wrote, “...Sea seems to to separate but alsu unify.” If members of various ethnic communities from Nusantara live side by side in coastal cities or have married each other in their new places with local population can be seen as a sign that they have integrated themselves to the existing communities, the question is: is this not an early sign of wider integration process, namely in nation-state? If sailors-traders formed a communication networks because they needed each other organized themselves in organizationssuch as the Ropelin because of being in similiar profession and mutual needs, is that not the roots of national integration? The existence of of inter-island shipping does not only to facilitate population mobility but to bring closer one with another in new places, allowing new member to enter and to integrate with the existing community